The Role of Personality in COVID-19-Related Perceptions, Evaluations, and Behaviors: Findings Across Five Samples, Nine Traits, and 17 Criteria. Issue 1 (January 2022) - Zettler, Ingo; Schild, Christoph; Lilleholt, Lau; Kroencke, Lara; Utesch, Till; Moshagen, Morten; Böhm, Robert; Back, Mitja D.; Geukes, Katharina
Individuals and institutions around the world have been affected by the coronavirus disease 2019 (COVID-19). Herein, we investigate the role of basic (Big Five and HEXACO) and specific (Dark Factor of Personality, Narcissistic Rivalry, and Narcissistic Admiration) personality traits for 17 criteria related to COVID-19, grouped into (i) personal perceptions in terms of risks and worries about the disease, (ii) behavioral adjustments in terms of following health recommendations and hoarding, and (iii) societal evaluations in terms of the appropriateness of different measures and feelings of social cohesion. (Internal) Meta-analytic results across five samples from two countries (overall N = 19, 718) show—next to gender and age effects—the importance of several traits, including Emotionality/Neuroticism for personal perceptions and anti- or prosocial traits for behavior in line with health recommendations. The investigation highlights the importance of individual differences in uncertain and changing situations in general and during the COVID-19 pandemic in particular.